2013
DOI: 10.1007/s10096-013-1814-z
|View full text |Cite
|
Sign up to set email alerts
|

Independent risk factors for the co-colonization of vancomycin-resistant Enterococcus faecalis and methicillin-resistant Staphylococcus aureus in the region most endemic for vancomycin-resistant Staphylococcus aureus isolation

Abstract: In the majority of cases of vancomycin-resistant Staphylococcus aureus (VRSA), vancomycin-resistant Enterococcus faecalis (VR E. faecalis) served as the vanA donor to S. aureus. Previous studies that evaluated the risk factors for co-colonization with VRE and MRSA did not differentiate between VR E. faecalis and VR E. faecium. This study aimed to identify variables associated with VR E. faecalis and MRSA co-colonization. A retrospective case-control study from January 2008 to December 2009 was conducted at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…The percentage of colonization by MRSA (6 %) upon admission or during ICU stay was low compared to the rates from international ICU departments [15]. The most plausible explanation for this low percentage may be attributed to prior implementation of a [16,17], this is the first study showing that enteric colonization by VRE predisposes to MRSA colonization upon ICU admission and during stay. A meta-analysis investigating risk factors for MRSA colonization upon hospital or ICU admission showed that VRE carriage increased the risk for MRSA by 3.12 times [18].…”
Section: Discussionmentioning
confidence: 77%
“…The percentage of colonization by MRSA (6 %) upon admission or during ICU stay was low compared to the rates from international ICU departments [15]. The most plausible explanation for this low percentage may be attributed to prior implementation of a [16,17], this is the first study showing that enteric colonization by VRE predisposes to MRSA colonization upon ICU admission and during stay. A meta-analysis investigating risk factors for MRSA colonization upon hospital or ICU admission showed that VRE carriage increased the risk for MRSA by 3.12 times [18].…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, in our study, patients with VR E. faecalis were frequently cocolonized with MRSA to a greater degree than patients with VS E. faecalis and uninfected controls. Furthermore, our team recently reported that the severity of illness, presence of indwelling devices, and chronic wounds are independent predictors for cocolonization with VR E. faecalis and MRSA (20). These findings, together with the growing prevalence of VR E. faecalis and the relatively high prevalence of Inc18-like plasmids in Michigan, might partially explain the endemicity of VRSA in this region (3,8).…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, observational studies have found an increased risk of cocolonization by resistant gastrointestinal bacteria when a patient is already colonized by bacteria resistant to different classes of antibiotics, possibly indicating that resistant bacterial strains are less likely to be competitively excluded by each other than by susceptible strains. Such a risk of cocolonization was found independently of other risk factors such as antibiotic usage and patient comorbidities (60,61). Finally, experimental results suggest that patients receiving fecal microbiota transplant of susceptible bacteria are less likely to be recolonized by resistant bacteria (62).…”
Section: Discussionmentioning
confidence: 92%